Analisis Antropometri Dan Koordinasi Mata Tangan Terhadap Keterampilan Pointing Atlet Petanque Sulawesi Selatan - Nurul Natasya; Sudirman Sudirman; Ahmad Rum; Saharullah Saharullah; Muh. Adnan Hudain (Departement of Mathematics Education, 2024)
This research is a type of quantitative descriptive research that uses a